2016
DOI: 10.3109/01612840.2015.1084554
|View full text |Cite
|
Sign up to set email alerts
|

Boredom in the Workplace: Reasons, Impact, and Solutions

Abstract: Boredom in the workplace is not uncommon, and has been discussed widely in the academic literature in relation to the associated costs to individuals and organizations. Boredom can give rise to errors, adverse patient events, and decreased productivity-costly and unnecessary outcomes for consumers, employees, and organizations alike. As a function of boredom, individuals may feel over-worked or under-employed, and become distracted, stressed, or disillusioned. Staff who are bored also are less likely to engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Managers may also take advantage of job crafting, as looking for novelty and innovation in one’s work has been shown to reduce work‐related boredom (Harju, Hakanen, & Schaufeli, 2016). Additional strategies, such as providing breaks, creating meaningful environments, using humor or developing effective time management skills have also been suggested (Cleary et al, 2016). Nevertheless, in the case of bored employees, managers should take into consideration that, although these workers benefit from these activities, they are usually less motivated to engage in such behaviors, being “trapped” in a negative spiral (Harju et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managers may also take advantage of job crafting, as looking for novelty and innovation in one’s work has been shown to reduce work‐related boredom (Harju, Hakanen, & Schaufeli, 2016). Additional strategies, such as providing breaks, creating meaningful environments, using humor or developing effective time management skills have also been suggested (Cleary et al, 2016). Nevertheless, in the case of bored employees, managers should take into consideration that, although these workers benefit from these activities, they are usually less motivated to engage in such behaviors, being “trapped” in a negative spiral (Harju et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Boredom is a subjective experience, as individuals may interpret a given situation differently. Nonetheless, factors such as limited interactions with colleagues, opportunities for progression or lack of options or inadequate resources contribute to the experience of boredom (Cleary, Sayers, Lopez, & Hungerford, 2016). It is a rather complex individual experience, as it often comes with conflicting behavioral patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they say that there is not a well-grounded theory on work boredom, but there are a few concepts established on boredom. Many studies point out that it has identified a range of individual and work-related factors that can be associated with workplace boredom; moreover, boredom does have an impact on job satisfaction, commitment and decreased productivity (Cleary, Sayers, Lopez, & Hungerford, 2016;Mael, & Jex, 2015;Whiteoak, & Mohamed, 2016). However, Velasco (2017) argue that recent literature suggests that workplace boredom goes beyond monotony; other studies focus on the possibility that some employees are boredom-prone by nature.…”
Section: Boredommentioning
confidence: 99%
“…Class-related boredom experienced by nursing students may affect their health (Deasy et al, 2016) and learning outcomes (Zhou et al, 2016). Therefore, elevating the task value and reducing the level of boredom are core goals in theoretical and practical research in education (Perkins and Hill, 1985;Pekrun et al, 2010) and nursing settings (Cleary et al, 2016).…”
Section: Introductionmentioning
confidence: 99%